Global Perspective on the Management of Peyronie's Disease - Moisés da Silva, Gabriel Veber; Dávila, Francisco Javier; Rosito, Tiago Elias; Martins, Francisco E. (Frontiers in Reproductive Health, 2022)
Introduction: Peyronie's disease results in penile curvature, shortening, or significant discomfort on erection, leading to difficulty in sexual activity and psychological distress. Despite extensive research, surgery remains the mainstay of treatment. Objective: We report the most common surgical procedures used in the correction of Peyronie's disease and suggest a surgical algorithm to guide its management. Methods: Using PubMed, we reviewed the published literature on the surgical treatment of Peyronie's disease and its outcomes. We identified original articles, review articles, and editorials addressing the subject, with a focus on surgical procedures, their indications, and outcomes. Results: Peyronie's disease refractory to conservative treatment, can be managed by corporoplasty and/or penile prosthesis implantation. Corporoplasty includes tunical shortening (convex side-shortening) plication procedures and tunical lengthening (concave side lengthening) incision/excision and grafting procedures if the erectile function is adequate. If refractory erectile dysfunction is present, placement of a penile prosthesis with or without further adjunctive straightening maneuvers is recommended. We reviewed the indications, advantages, disadvantages, and outcomes of the available techniques and proposed a surgical treatment algorithm. Conclusion: Penile shortening procedures are usually indicated in curvatures <60°, in penises with adequate length. Partial excision/incision and grafting are indicated for curvatures >60°, hourglass or hinge deformities, and short penises, if the patient's erectile function is adequate. The presence of "borderline" erectile function and/or ventral curvature tilts the choice toward shortening procedures, and refractory erectile dysfunction is an indication for penile prosthesis placement. An accurate risk/benefit assessment of the individual patient as well as meticulous patient counseling are critically important